2022
DOI: 10.28991/cej-2022-08-07-014
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of Suburban Industrial Development through Place Attachment

Abstract: This research uses urban space reconstruction as the entry point, discussing the characteristics of residents’ sense of place in Lingang new town, Shanghai, based on the method of factor analysis to divide the sense of place into place attachment, place identity, and place dependence. On the whole, residents’ sense of place in Lingang new town is at a common level, and the comprehensive score of residents’ sense of place in Lingang new town is "more than half". Meanwhile, place attachment is the highest, place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Place dependence is referred to as functional attachment to a place (Stokols and Shumaker, 1981). It is the perceived strength of the bond between people and places (Lu et al, 2022). Place affect is defined as the emotional bond people share with environmental settings (Ramkissoon, 2016), fosterage of psychological restorativeness (Ramkissoon, 2020), and a good feeling factor (Ramkissoon, 2021).…”
Section: Place Attachmentmentioning
confidence: 99%
“…Place dependence is referred to as functional attachment to a place (Stokols and Shumaker, 1981). It is the perceived strength of the bond between people and places (Lu et al, 2022). Place affect is defined as the emotional bond people share with environmental settings (Ramkissoon, 2016), fosterage of psychological restorativeness (Ramkissoon, 2020), and a good feeling factor (Ramkissoon, 2021).…”
Section: Place Attachmentmentioning
confidence: 99%
“…They concluded there can be a positive relationship between an industrial cluster and the localities within which their workers reside, even in times of sustainability transitions such as decarboinsaion. Continuing on the deacrbonisation theme, Lu concluded that different precinct locations generate a connection with the respective workforces (local community) and that they respond differently to negative distruption (Lu et al, 2022). The energy transition therefore needs to bring the local people (workforce and community) along on the journey, thus identifying a relationship between industry and its local workforce.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scholars have tended to identify changes in the material spaces from the perspective of land use and cover with the help of satellite images [8,9]. By analyzing the forms of urban agglomeration, a deeper understanding of the process of spatial agglomeration and diffusion can be achieved using GIS [10][11][12], eventually leading to clear policy recommendations [13][14][15]. Research methods also continue to go deeper into the fields of artificial intelligence, sensors, and cloud computing, and optimization strategies are deeply discussed with scenario simulations [16,17].…”
Section: Introductionmentioning
confidence: 99%